Pengembangan Sumber Daya Manusia di Madrasah: Menyelaraskan Kompetensi Guru dengan Tujuan Institusi - Asngad, To’in; Hanif, Muh. (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
This study aims to analyze human resource management in an Islamic educational institution located in Purbalingga. It focuses on exploring the strategic steps employed by Madrasah Aliyah Negeri (MAN) Purbalingga to align teacher development with the school’s vision, mission, and goals. Using a qualitative case‐study approach, data were collected through in-depth interviews, observations, and document review involving purposively selected school leaders: the principal, vice‐principal, and teaching and administrative staff. The findings reveal six strategic steps: (1) socialization and internalization of the vision and mission by teachers; (2) integration of HR development programs based on needs assessments; (3) strengthening pedagogical competence, Islamic character, and technological literacy; (4) alignment of performance appraisal with institutional success indicators; (5) emphasis on sustainability through digital evaluation and monitoring cycles; and (6) consistent policy support embedded in strategic planning and budgeting documents. The implementation of these steps successfully establishes strategic alignment, enhances teacher professionalism and spirituality, and contributes to improved teaching quality and student character development. These findings enrich the Strategic Human Resource Development framework by adding a religious dimension in the context of Islamic education and produce an adaptive six-step conceptual model for use in other madrasahs.